F(x1,x2,x3)= x 1 2 +2x 2 2 +5x 3 2 +2x 1 x 2 +2x 1 x 3 +6x 2 x 3 的标准形为()
举一反三
- $(-x-1)(x^{4}+2x^{3}-x^{2}-4x-2)+(x+2)(x^{4}+x^{3}-x^{2}-2x-2)$的结果是( )。 A: $x^{2}-2$; B: $x^{3}-x^{2}-1$; C: $2x^{3}-4x-2$; D: $x^{4}+3x-2.$
- 下列计算结果正确的是() A: (﹣2x 2)^3=﹣6x^6 B: x^2x^3 =x^6 C: 6x^4÷3x3 =2x D: x^2 +x^3 =2x^5
- 求方程组的解,取初值为(1,1,1)。[img=250x164]180333307ab8fde.jpg[/img] A: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fsolve(f,[1,1,1],optimset('Display','off')) B: x=fsolve(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1]) C: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fzero(f,[1,1,1]) D: x=fzero(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1])
- 求函数$y = {{1 + \root 3 \of {{x^2}} - \sqrt {2x} } \over {\sqrt x }}$的导数$y' = $( ) A: $ {1 \over 2}{x^{ - {3 \over 2}}} + {1 \over 6}{x^{ - {5 \over 6}}}$ B: $ - {1 \over 2}{x^{ - {3 \over 2}}} + {1 \over 6}{x^{ - {5 \over 6}}}$ C: ${1 \over 2}{x^{ - {3 \over 2}}} - {1 \over 6}{x^{ - {5 \over 6}}}$ D: ${1 \over 3}{x^{ - {3 \over 2}}} - {1 \over 6}{x^{ - {5 \over 6}}}$
- 函数\(y = {x^{ - 4}}{\rm{ + }}2{x^3} - 2x\)的导数为( ). A: \(4{x^3} + 6{x^2} - 2\) B: \( - 4{x^{ - 5}} + 6{x^2} - 2\) C: \( - 4{x^{ - 3}} + 6{x^2} - 2\) D: \( - 4{x^3} + 6{x^2} - 2\)